Hydraulic traits explain differential responses of Amazonian forests to the 2015 El Niño-induced drought - de V. Barros, Fernanda; Bittencourt, Paulo R. L.; Brum, Mauro; Restrepo-Coupe, Natalia; Pereira, Luciano; Teodoro, Grazielle S.; Saleska, Scott R.; Borma, Laura S.; Christoffersen, Bradley O.; Penha, Deliane; Alves, Luciana F.; Lima, Adriano J. N.; et al. (The New phytologist, 2019)
Reducing uncertainties in the response of tropical forests to global change requires understanding how intra- and interannual climatic variability selects for different species, community functional composition and ecosystem functioning, so that the response to climatic events of differing frequency and severity can be predicted. Here we present an extensive dataset of hydraulic traits of dominant species in two tropical Amazon forests with contrasting precipitation regimes – low seasonality forest (LSF) and high seasonality forest (HSF) – and relate them to community and ecosystem response to the El Niño–Southern Oscillation (ENSO) of 2015. Hydraulic traits indicated higher drought tolerance in the HSF than in the LSF. Despite more intense drought and lower plant water potentials in HSF during the 2015-ENSO, greater xylem embolism resistance maintained similar hydraulic safety margin as in LSF. This likely explains how ecosystem-scale whole-forest canopy conductance at HSF maintained a similar response to atmospheric drought as at LSF, despite their water transport systems operating at different water potentials. Our results indicate that contrasting precipitation regimes (at seasonal and interannual time scales) select for assemblies of hydraulic traits and taxa at the community level, which may have a significant role in modulating forest drought response at ecosystem scales.